IMPACT OF LIQUIDITY AND SOLVENCY ON PROFITIBALITIAS ON PT. CHANDRA ASRI PETROCHEMICAL, TBK.: Current Ratio, Debt to Total Assets Ratio, Return On Assets. - Firli Firli (Universitas Serang Raya, 2020)
The research aims to determine the partial and simultaneous influence of current Ratio, Debt to Asset Ratio, on Return on Asset at PT. Chandra Asri Petrochemichal, TBK. Year 2010-2019. The Data used is sourced from the financial statements at PT. Chandra Asri Petrochemichal, Tbk in the form of balance sheet and Income Statement report or annual Reprort. After the data is collected, it is analyzed by using classic assumption test model, double Linear regression, determination and hypothesis test. The classic assumption test Model used the normality test, autocorrelation test, multicolinearity test, while the hypothesis test is test T and test F. Based on analysis results of research hypothesis testing results at a confidence level of 95% showed that the simultaneous liquidity (CR) and solvency (DAR) to the profitability (ROA) did not have a significant influence on PT. Chandra Asri Petrochemichal, TBK. And it also partially did not have a significant influence on PT. Chandra Asri Petrochemichal, TBK.